A training and implementation model for head and neck oncology service delivery in Mozambique. Issue 3 (June 2022) - Chulam, Thiago C.; Bambo, Arquimedes Wamarremula Pedro; Machava, Pedro Rafael; Kowalski, Luiz P.
Abstract : Purpose of review: There is an extreme shortage of head and neck surgeons in Africa. In Mozambique prior to 2000, there were no surgeons with specific training in head and neck surgical oncology. Here, we introduce a training model and report our experience with implementation following the training of the first two head and neck surgeons from Mozambique. Recent findings: This training program, undertaken in Brazil, facilitated the formation of the first two head and neck surgeons from Mozambique. These surgeons received comprehensive training in head and neck surgical oncology and multidisciplinary care, allowing them to then treat their patients under continuous online mentorship collaboration. This model is expected to help in the local formation of new specialists and in the establishment of this specialty in Mozambique. Summary: The program started with remote training and support provided by the MD Anderson Cancer Center, in Texas, USA, as part of the Extension for Community Healthcare Outcomes program. Further training was then undertaken at an established fellowship program in Brazil as a focal point for 2 years, and the knowledge gained was replicated and disseminated locally.